Theoretical evaluation of the malathion and its chemical derivatives interaction with cytosolic phospholipase A2 from zebrafish - Manzi, Agatha [UNESP]; De-Carli, Bruno Paes [UNESP]; Roggero, Airam [UNESP]; Ferreira De Moraes, Laila Lucyane [UNESP]; Annunciato, Isabelly [UNESP]; Novo Belchor, Mariana [UNESP]; Lima Neto, Daniel Ferreira De; Antonio De Oliveira, Marcos [UNESP]; Hikari Toyama, Marcos [UNESP] (Elsevier, 2023)
Cytosolic phospholipase A2 (cPLA2) belongs to a large family of proteins and plays a crucial role in the regulation of arachidonic acid metabolism and inflammation cascade in zebrafish (Danio rerio). This enzyme with a molecular weight of 85 kDa, has two distinct domains. One is the regulatory and calcium-dependent (Ca2+) domain called C2, the other is the catalytic α/β hydrolase Ca2+-independent domain, where serine and aspartic acid catalytic dyad residues are present. We investigated the interaction of malathion and their organophosphate metabolites in the cPLA2 using in silico tools. Molecular docking results showed hydrophobic interactions with the paraoxon and catalytic site residue (Ser 223). Malathion increases intracellular Ca2+ due to endoplasmic reticulum influx which in turn activities phospholipase A2 and arachidonic acid release. Molecular docking and homology modelling of proteins and ligands could be a complementary tool for ecotoxicology and environment pollution assessment.
Keywords: Docking molecular; Organophosphates; Phospholipase A2; Xenobiotics